Korelasi Status Gizi dengan Phase Angle pada Pasien Gagal Ginjal Kronis yang Menjalani Hemodialisis - Hartanto, Okky; Puruhita, Niken; Khairuddin, Khairuddin; Muis, Siti Fatimah; Christianto, Febe (Medica Hospitalia : Journal of Clinical Medicine, 2023)
BACKGROUND: Nutritional problem are often experienced by patients with chronic kidney disease (CKD) undergoing regular hemodialysis. There are various tools that can be used to evaluate nutritional status, such as the 7-point Subjective Global Assessment (SGA), nevertheless, malnutrition in these patients is still underdiagnosed and resulting in worse clinical outcomes. Phase Angle (PhA) as measured by multi-frequency Bioelectrical Impedance Analysis (BIA) may detect nutritional problem in early stage in order to start nutrition therapy early. OBJECTIVE: To analyze correlation between nutritional status and PhA in CKD patients with regular hemodialysis. METHODS: The subject of this study were 39 CKD patients undergoing regular hemodialysis who met the inclusion and exclusion criteria. Nutritional status was evaluated by 7-point SGA, while PhA was measured by multi-frequency BIA. Correlation between variables analyzed by Spearman correlation test. RESULT: Positive correlation was observed between nutritional status and PhA (r = 0,64; p < 0,001). There was a negative correlation between PhA and number of comorbids (r = -0,381, p = 0,017). PhA was not correlated with sex and hemodialysis duration. CONCLUSION: There is positive correlation between nutritional status measured by 7-point SGA and PhA in CKD patients with regular hemodialysis.